P No Bosses: A Worker Experience of Labor Organization, Bateas Mine, Atacama, Chile. 1969-1973 - Venegas-Valdebenito, H (UNIV CATOLICA NORTE, 2021)
This article reconstructs the activity of a mining cooperative in its concrete experience in the critical juncture of 1969-1973 in Chile. Cooperative work was promoted by the State as a proposal for social transformation, but at the same time as a palliative to the high unemployment rates in the province of Atacama. He encouraged the organization of mining cooperatives, put in tension the margins of freedom displayed by the traditional pirquineros, on the one hand, and the demand for a systematic, continuous and organized effort, on the other. Difficult problem to assess among workers who exhibited a propensity to an itinerant life and occasional subordination.